On the Verge between Retranslation and Revision: Revisiting Translations of Modernist Novels in Türkiye - İrem Ceren Doğan (English Studies at NBU, 2023)
This research aims to elucidate the underlying forces that propelled the first translators to reprocess their texts within the framework of modernist literature, and to reveal the nature of these reprocessed texts as retranslations or revisions. The corpus of this study is composed of modernist novels To The Lighthouse (1927), Lolita (1955), Heart of Darkness (1899), and Nightwood (1936). The first translators of these novels into Turkish felt the need to reprocess texts over long periods. The second versions could be classified as retranslations according to the characteristics outlined by the retranslation hypothesis. However, considering the limitations of this hypothesis, particularly regarding retranslations from the 2000s onward, it seems insufficient to explain current dynamics. To establish a clear differentiation between revision and retranslation, it is essential to conduct a comprehensive comparative analysis of the first and subsequent versions. Based on the analysis, it has been determined that there are limited but significant changes in the revised texts. While the number of alterations may not reach statistical significance to label them as "retranslations", they can be categorized as "revisions." It has been concluded that the triggering factors behind the revisions are related to the changing sociocultural factors, patronage and the habitus of the translators.